PENINGKATAN PRESTASI BELAJAR SISWA MELALUI MODEL JIGSAW LEARNING PADA KOMPETENSI DASAR IKATAN KIMIA - sri utami (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The material chemical bond is a complicated matter because memorization combined with reasoning, and just imagining something we can not see and we observe directly, making the student saturated and misinterpretation if only to hear the teacher to review the material. For that we should bear Jigsaw Learning Model we apply to dispose of burnout and boredom of students, so that students interested in chemical bonding materials and ambition to get achievement in basic competencies chemical bonds. Literally learning model is a strategy to enhance learning motivation, learning attitude among students, capable of critical thinking, social skills and achieving a more optimal learning outcomes. That's why the development of the traditional learning model is becoming obsolete replaced by modern learning model. One of them learning model Jigsaw Learning. From these results, the model of Jigsaw Learning is seen that the class X-2 JIGSAW LEARNING higher values ​​with mastery 83%, while the control class X-1 value with 69% mastery.